A novel BCC-L21-BCC hierarchical heterostructure high entropy alloy with excellent corrosion resistance and mechanical properties in as-cast state - Shuai Hu; Junyang Zheng; Guangzeng Zhang; Jiakai Xing; Ran Wei; Tan Wang; Shaojie Wu; Yongfu Cai; Shaokang Guan; Fushan Li; Chen Chen (Journal of Materials Research and Technology)
In this paper, a novel as-cast CrFeNiAl0.35Si0.1Ti0.1 high entropy alloy (HEA) with micron-to-nano hierarchical heterostructure was designed, and its microstructure, mechanical properties and corrosion resistance have been systematically investigated. It is found that, this novel HEA exhibits well-dispersed L21 phase with various sizes from micron-scale to nano-scale in the BCC matrix, while nano-sized BCC lamellas could also emerge in the L21 phase with large diameter. Moreover, this HEA exhibits not only excellent corrosion resistance in 3.5 wt% NaCl solution that close to super-stainless steels, but also high mechanical properties combining yield strength of 1712 ± 56 MPa, compressive plasticity of 21.2% ± 0.5% and hardness of ∼560 Hv. Such outstanding comprehensive properties for this HEA are possibly resulted from the complex hierarchical BCC-L21-BCC heterostructure with stable passive film and low diversity in work function between different phases. This work provides a novel route in the development of high-performance corrosion-resistant HEAs for structural and coating applications.